Shape‐Memory Hydrogels with Crystallizable Oligotetrahydrofuran Side Chains. Issue 1 (November 2014) - Balk, Maria; Behl, Marc; Nöchel, Ulrich; Lendlein, Andreas; Lendlein, Andreas; Domb, Abraham J.
Summary Stimuli‐sensitive materials, such as shape‐memory polymers (SMP) have attracted tremendous interest in the field of biomedical applications and Regenerative Therapies. In case of implants intended for soft tissue, adequate elastic properties can be mimicked by water swollen hydrophilic polymer networks (i.e. hydrogels) and can be equipped with a shape‐memory capability. Shape‐memory hydrogels (SMHs) having body compatible transition temperatures (Ttrans) have not been reported so far. Here we explored, whether SMHs with Ttrans ≤ 37 °C could be created consisting of the hydrophilic poly(N‐vinyl pyrrolidone) segment, the crosslinker oligo(ethylene glycol) dimethacrylate (OEGDMA, Mn = 370 g · mol−1), and grafted crystallizable oligotetrahydrofuran (OTHF, Mn = 7.100 g · mol−1, Tm = 31 °C) segments as switching domains. As function of the OTHF content (30–75 wt%), the hydrogels had a degree of swelling between 450 and 3200%, a Ttrans about 26 °C, and soft mechanical properties in the kPa range. Therefore, these SMHs might be interesting biomaterial candidates e.g. as smart implants.